Symposium 4: Disrupting the illusion of sameness: The importance of making place visible in online learning - Sheail, Philippa; Ross, Jen (Proceedings of the International Conference on Networked Learning, 2014)
This article challenges what the authors consider to be the potential for ‘illusions of sameness’ in online learning in higher education. Drawing on the work of Dall’Alba and Barnacle (2005) and Sidhu and Dall’Alba (2012) on disembodied education, and on work by Ross et al (2013) on ‘making distance visible’, the authors consider strategies for ‘bringing the outside in’ in digital education. If we accept that the local context of the student is important, and recognise the significance of bodies and embodied knowing, particularly in relation to professional practice, in online learning environments, the authors ask what strategies educators might adopt in terms of recognising and communicating bodies and locales in digital spaces. How might the illusion of sameness be disrupted? Two examples of disruption from the MSc in Digital Education at the University of Edinburgh are outlined: the participant map, and the digital postcard.